Spore Cortex Hydrolysis Precedes Dipicolinic Acid Release during Clostridium difficile Spore Germination - Francis, Michael B.; Allen, Charlotte A.; Sorg, Joseph A. (Journal of bacteriology, 2015)
Bacterial spore germination is a process whereby a dormant spore returns to active, vegetative growth, and this process has largely been studied in the model organism Bacillus subtilis . In B. subtilis , the initiation of germinant receptor-mediated spore germination is divided into two genetically separable stages. Stage I is characterized by the release of dipicolinic acid (DPA) from the spore core. Stage II is characterized by cortex degradation, and stage II is activated by the DPA released during stage I. Thus, DPA release precedes cortex hydrolysis during B. subtilis spore germination. Here, we investigated the timing of DPA release and cortex hydrolysis during Clostridium difficile spore germination and found that cortex hydrolysis precedes DPA release. Inactivation of either the bile acid germinant receptor, cspC , or the cortex hydrolase, sleC , prevented both cortex hydrolysis and DPA release. Because both cortex hydrolysis and DPA release during C. difficile spore germination are dependent on the presence of the germinant receptor and the cortex hydrolase, the release of DPA from the core may rely on the osmotic swelling of the core upon cortex hydrolysis. These results have implications for the hypothesized glycine receptor and suggest that the initiation of germinant receptor-mediated C. difficile spore germination proceeds through a novel germination pathway. IMPORTANCE Clostridium difficile infects antibiotic-treated hosts and spreads between hosts as a dormant spore. In a host, spores germinate to the vegetative form that produces the toxins necessary for disease. C. difficile spore germination is stimulated by certain bile acids and glycine. We recently identified the bile acid germinant receptor as the germination-specific, protease-like CspC. CspC is likely cortex localized, where it can transmit the bile acid signal to the cortex hydrolase, SleC. Due to the differences in location of CspC compared to the Bacillus subtilis germinant receptors, we hypothesized that there are fundamental differences in the germination processes between the model organism and C. difficile . We found that C. difficile spore germination proceeds through a novel pathway.